Enhanced Formation of α-Tocopherol and Highly Oxidized Abietane Diterpenes in Water-Stressed Rosemary Plants - Munné-Bosch, Sergi (American Society of Plant Physiologists, 1999)
The lipid-soluble antioxidants α-tocopherol and carnosic acid were studied in field-grown rosemary (Rosmarinus officinalis L.) plants subjected to drought. During summer in the Mediterranean region, the predawn water potential decreased to −3 MPa and the relative water content to 42%, which caused a depletion of the maximum diurnal CO(2) assimilation rate by 80%. Meanwhile, the maximum efficiency of photosystem II photochemistry and the chlorophyll content of leaves remained unaltered, indicative of the absence of photooxidative damage. The concentration of α-tocopherol increased by 15-fold and that of carotenoids by approximately 26% in response to water stress. Enhanced formation of the highly oxidized abietane diterpenes isorosmanol (by 25%) and dimethyl isorosmanol (by 40%) was observed during the summer as result of the oxidation of carnosic acid, which decreased by 22%. The large amounts of carnosic acid, α-tocopherol, and carotenoids present in rosemary leaves might contribute to the prevention of oxidative damage in plants exposed to drought.